2014
DOI: 10.1007/s13197-014-1420-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential assessment of Rumex vesicarius L. as a source of natural antioxidants and bioactive compounds

Abstract: The present work is designed to evaluate the antioxidant activities of hydroalcoholic extract (HAE) and its fractions (viz., hexane (HF), chloroform (CF), ethyl acetate (AF), n-butanol (BF) and water (WF)) obtained from aerial part of Rumex vesicarius L. by using different in vitro antioxidant assays. The content in pigments (carotenoids and chlorophylls), total phenolics, flavonoids and tannins were determined using spectrophotometric methods. Qualitative analyses of major phenolics by TLC analysis were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The uses of synthetic antioxidants in food products were restricted owing to their instability and to their suspected action as carcinogenesis promoters (Namiki, ). Therefore, there has been an increasing tendency via the usage of natural alternative sources generally present in plants (Beddou, Bekhechi, Ksouri, Sari, & Atik Bekkara, ). Essential oils and phenolic compounds, extracted from many plants, have recently gained popularity and scientific interest as natural preservatives in food industry.…”
Section: Introductionmentioning
confidence: 99%
“…The uses of synthetic antioxidants in food products were restricted owing to their instability and to their suspected action as carcinogenesis promoters (Namiki, ). Therefore, there has been an increasing tendency via the usage of natural alternative sources generally present in plants (Beddou, Bekhechi, Ksouri, Sari, & Atik Bekkara, ). Essential oils and phenolic compounds, extracted from many plants, have recently gained popularity and scientific interest as natural preservatives in food industry.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment with the highest reducing power was the solution of 10 mg/mL of water extract with an absorbance value of 0.55. Furthermore, many studies performed with different plant species such as Eruca sativa [Sarwar Alam et al 2007], Rumex vesicarius [Beddou et al 2015], Artemisia annua [Wan et al 2016] and Momordica charantia [Svobodova et al 2017] in previous years revealed that reducing power activity increased in concentration-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…This result concurred with Tekwu et al [30] and Djellouli et al [31] who reported that chloroform fraction derived from the methanol extract of A. radiata was found to be most effective followed by ethyl acetate and butanol fractions. Some extracts showed weakly anticandidal activity [8]. El Hassany et al [14] reported that 9α-hydroxyparthenolide isolated in A. radiata at a concentration of 50 and 100 µg/disc, inhibited the growth of Bacillus cereus (IPL 58605), Streptococcus C (IPT 2-035), Proteus vulgaris (CIP 58605), Enterococcus faecalis (CIP 103214) and Escherichia coli (CIP 54127).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Its leaves attenuated in petioles, are toothed or sub-pinnative; its inflorescences, heads with spinescent involucres are formed of yellow orange florets, the outside one 25 mm long. A. radiata is commonly known in Arabic Nogd sahrâwi Nogd Lhor [8] and in Tamazight "Ajjerg; âwjerg" is also called Arabian oxeye [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation